Development Of Cognitive Diagnostic Assessment To Measure The Mastery Level Of Factorisation Of Algebraic Fractions Among Form Two Students. - Noor, Mohd Azizi Mohd (2024)
Cognitive Diagnostic Assessment (CDA) is one of the assessments recommended by the Ministry of Education of Malaysia based on the Malaysia Education Blueprint 2013-2025 to measure students’ cognitive development. This assessment is crucial as it provides in-depth information about students’ learning needs and enables teachers to design more effective instruction to help students achieve their learning goals. With a focus on cognitive development, students can be provided with more targeted and appropriate support to enhance their achievement in this area. Thus, this study aims to develop and assess a CDA focusing on form two students’ mastery of factorisation of algebraic fractions. The CDA development involved two stages: establishing expert and student response based cognitive models. Expert mathematics teachers constructed the expert-based cognitive models, which were evaluated by a panel of content and psychometric experts. The validation process used different criteria, including items and attributes development based on Bloom's taxonomy hierarchy, items clarity, and alignment with form two standards document curriculum and assessment (SDCA) for Form Two Mathematics. Then, 30 ordered multiple choice (OMC) items were tested on 159 students from National Secondary Schools. The assessment revealed that the CDA's cognitive models had good discrimination ability, except for items deemed too easy. Each item had appropriate distractors, and the CDA versions showed reliability in terms of consistency and correlation between expert-based and student response-based cognitive models.